PENGGUNAAN JERUK NIPIS (Citrus aurantifolia) DAN LIDAH BUAYA (Aloe vera L.) SEBAGAI SEDIAAN HAIR TONIC - Nurita, Elly; Thaib, Cut Masyithah; Adiansyah, Adiansyah; Hutasoit, Irmayanti (Jurnal Farmanesia, 2018)
Lignin compounds and polysaccharides, the nutritious substances in aloe vera, are useful as a carrier for the nutrients needed by the skin to repair hair roots, strengthen and stimulate hair growth. The purpose of this study was to determine the efficacy of the combination of lime extract and aloe vera extract as a hair tonic preparation for hair growth. Lime and aloe vera extracts were obtained by maceration method using 96% ethanol as solvent. The combination of lime extract and aloe vera extract is formulated to be a hair tonic, with a combination of 1 (1%:1%), combination 2 (2%:1%), and combination 3 (1%:2%). Then evaluate the stability of the hair tonic preparation, homogeneity, pH, hair growth activity, and hair weight of rabbits. The results of the stability test of the hair tonic preparation of a combination of lime extract and aloe vera extract did not change color, shape, and odor. The results of the homogeneity examination of the formulations of formulas 1, 2, and 3 were homogeneous. The result of pH observation was that the higher the concentration of the combination of lime extract and aloe vera extract, the higher the pH of the preparation. The results of the measurement of rabbit fur length showed that the highest hair growth rate was formula 3 combinations (1%:2%). The results of the three formulations of the combination of lime extract and aloe vera extract showed that the longer the hair growth of the rabbit, the heavier the weight of the rabbit's hair.